2019
DOI: 10.1002/jmor.20979
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between habitat use and body shape in geckos

Abstract: Geckos are a highly diverse group of lizards, with more than 1,700 species that exhibit a wide range of behaviors, ecologies, and sizes. However, no study has examined links between habitat use and body shape in pad-bearing geckos. We set out to answer a basic question using a data set of padbearing geckos (112 species, 103 pad-bearing, 9 padless, 42 genera): Do geckos that occur in different habitats also differ in body shape? Overall, we found that body shape was surprisingly similar among our sample of pad-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 73 publications
1
8
0
Order By: Relevance
“…Indeed, Kulyomina et al. (2019) found that pad‐less gecko species have longer limbs than pad‐bearing ones (a result also borne out by our own data, especially for large‐bodied species; results not shown) – and found little shape differences between arboreal, saxicolous and terrestrial pad‐bearing geckos. Zaaf and Van Damme (2001) examined the limb proportions of 29 gecko species in an attempt to identify differences between climbing and ground‐dwelling species.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Indeed, Kulyomina et al. (2019) found that pad‐less gecko species have longer limbs than pad‐bearing ones (a result also borne out by our own data, especially for large‐bodied species; results not shown) – and found little shape differences between arboreal, saxicolous and terrestrial pad‐bearing geckos. Zaaf and Van Damme (2001) examined the limb proportions of 29 gecko species in an attempt to identify differences between climbing and ground‐dwelling species.…”
Section: Discussionsupporting
confidence: 81%
“…In contrast, climbing species occupying arboreal and saxicolous microhabitats would require greater stability and encounter fewer obstacles, allowing for faster rates of movement, and thus, evolve longer limbs (Foster et al., 2018; Goodman et al., 2008; Tan et al., 2020, but see Hagey et al., 2017 who showed that arboreal species had shorter femora, and Kaliontzopoulou et al, 2010 who showed terrestrial species had longer femora than scansorial species). Whilst these patterns have been observed within skinks (Foster et al., 2018; Goodman et al., 2008; Melville & Swain, 2000), attempts to link limb morphology and microhabitat use in non‐anoline lizards have often failed (e.g., Foster et al., 2018; Kulyomina et al., 2019; Olberding et al., 2016). The ecological and morphological similarities between many lizard groups, however, make further investigation into microhabitat–morphology relationships in lizard species potentially illuminating.…”
Section: Introductionmentioning
confidence: 99%
“…However, we hypothesize that a more parsimonious scenario is that the ancestor of the Bornean and Philippine species, excluding the clade comprising C. consobrinus , C. malayanus , and C. limajalur , was a small‐bodied forest dweller with blotched color pattern similar to C. pubisulcus . This evolutionary pattern of general‐bodied geckos, often with spotted or blotched coloration, giving rise to diverse clades has occurred across the greater gecko phylogeny, including the earliest gecko lineage (Allen et al, 2019; Kulyomina et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, the practice of using basic habitat categorizations from the literature is well‐accepted (e.g. Hsiang et al., 2015; Kulyomina et al., 2019), and these habitat categorizations can be considered to be estimates of primary habitat use. We accounted for the effect of body length (as a covariate) in these analyses in cases where body length was significantly related to the skin surface variable of interest.…”
Section: Qusto Program and Working Examplementioning
confidence: 99%